Los otros osos - Thompson, Michael, 1977- (Cambridge, Massachusetts : Star Bright Books, 2013)
"Mother and Father Koala are suspicious of the 'other' bears. They don't like the panda bears and they don't trust the polar bears. But their grumpiness melts away as they watch their little Koalas play together with 'other' bears"--
First published in English in Australia by Fremantle Press in 2010.
4-7.
P-2.
Keywords: Koala -- Juvenile fiction; Bears -- Juvenile fiction; Toleration -- Juvenile fiction; Spanish language materials -- Bilingual